2017
DOI: 10.15171/jcs.2017.027
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Medical Recording Training on Quantity and Quality of Recording in Gynecology Residents of Tabriz University of Medical Sciences

Abstract: Introduction: Medical records contain valuable information about a patient's medical history and treatment. Patient safety is one of the most important dimensions of health care quality assurance and performance improvement. Completing the process of documentation is necessary to continue patient care and continuous quality improvement of basic services. The aim of the present study was to evaluate the effect of medical recording education on the quantity and quality of recording in gynecology residents of Tab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…These challenges can impede their ability to consistently and effectively fill out medical records, despite their knowledge. Therefore, doctors must be aware and motivated to adhere to a standardized medical record [17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…These challenges can impede their ability to consistently and effectively fill out medical records, despite their knowledge. Therefore, doctors must be aware and motivated to adhere to a standardized medical record [17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…The research carried out on resident doctors reported an increase in the quality of medical record documents after training activities/workshops. [20][21][22] A similar study in an Ethiopian hospital stated that the presence of training interventions significantly increased the completeness of filling in medical records. 23 Dewi and Agustina stated that medical officers' compliance, such as those in charge, is lacking due to their business.…”
Section: Resultsmentioning
confidence: 99%